Analysis of information received during treatment and adherence to tamoxifen in breast cancer patients - Cruz, Aline; Rodrigues, Aline; Ferracini, Amanda; Stahlschmidt, Rebeca; Silva, Nice; Mazzola, Priscila (Contemporary Oncology/Współczesna Onkologia, 2017)
This study examines whether women with breast cancer, who are adherent and non-adherent to tamoxifen, differ in their perceptions of information received during treatment. This cross-sectional study included women receiving tamoxifen as adjuvant treatment for breast cancer recruited from a teaching hospital specialised in women’s health in the state of São Paulo (Brazil). Women were interviewed and their records were reviewed for socio demographic data and clinical characteristics. We assessed tamoxifen adherence using the Morisky-Green Test, and the European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire – Information module (EORTC QLQ-INFO25) was used to evaluate the information received by the women. The sample contained 31 women (mean age = 55.4; SD = 11.6 years). According to the Morisky-Green Test, 74.2% of the women had suboptimal tamoxifen adherence. The global score for women’s perceptions of information they received about the treatment and disease was 57.0 ±19.1 on a scale of 0 to 100, and no significant differences in scores were observed between adherents and non-adherents. A high prevalence of suboptimal tamoxifen adherence was observed. We found no significant differences between women with breast cancer who were adherent and non-adherent to tamoxifen.